Recommendations for optimal interdisciplinary management and healthcare settings for patients with rare neurological diseases - Graessner, Holm; Reinhard, Carola; Bäumer, Tobias; Baumgärtner, Annette; Brockmann, Knut; Brüggemann, Norbert; Bültmann, Eva; Erdmann, Jeanette; Heise, Kirstin; Höglinger, Günter; Hüning, Irina; Kaiser, Frank J.; et al. (Orphanet journal of rare diseases, 2024)
Background: In 2017, the German Academy for Rare Neurological Diseases (Deutsche Akademie für Seltene Neurologische Erkrankungen; DASNE) was founded to pave the way for an optimized personalized management of patients with rare neurological diseases (RND) in all age groups. Since then a dynamic national network for rare neurological disorders has been established comprising renowned experts in neurology, pediatric neurology, (neuro-) genetics and neuroradiology. DASNE has successfully implemented case presentations and multidisciplinary discussions both at yearly symposia and monthly virtual case conferences, as well as further educational activities covering a broad spectrum of interdisciplinary expertise associated with RND. Here, we present recommendation statements for optimized personalized management of patients with RND, which have been developed and reviewed in a structured Delphi process by a group of experts. Methods: An interdisciplinary group of 37 RND experts comprising DASNE experts, patient representatives, as well as healthcare professionals and managers was involved in the Delphi process. First, an online collection was performed of topics considered relevant for optimal patient care by the expert group. Second, a two-step Delphi process was carried out to rank the importance of the selected topics. Small interdisciplinary working groups then drafted recommendations. In two consensus meetings and one online review round these recommendations were finally consented. Results: 38 statements were consented and grouped into 11 topics: health care structure, core neurological expertise and core mission, interdisciplinary team composition, diagnostics, continuous care and therapy development, case conferences, exchange / cooperation between Centers for Rare Diseases and other healthcare partners, patient advocacy group, databases, translation and health policy. Conclusions: This German interdisciplinary Delphi expert panel developed consented recommendations for optimal care of patients with RND in a structured Delphi process. These represent a basis for further developments and adjustments in the health care system to improve care for patients with RND and their families.
Gesehen am 28.06.2024